THE BORNEAN GENUS HYPOBATHRUM (RUBIACEAE) AN INVESTIGATION OF ITS CHARACTERS AND TAXONOMIC STATUS - Mulyaningsih, Tri -; Ridsdale, Colin Ernest (Research Center for Biology, 2002)
MULYANINGSIH, TRI. & RIDSDALE, C. E. 2002. The Bornean genus Hypobathrum (Rubiaceae). An investigation of its characters and taxonomic status. Reinwardtia 12(1): 95â116.The investigation on the characters and taxonomic status of the Bornean genus Hypobathrum was based on morphological observations of 140 specimens in Herbarium Borgoriense. The present study shows that there are 24 species that can be recognised. There are six species already placed in the genus (H. frutescens, H. longifolium, H. microcarpum, H. racemosum, H. salicinum and H. venulosum), three species require new combinations (H. coniocarpum, H. gracile, and H. rufidulum), one species requires a new combination and a new status (H. hirtum), a new name in Hypobathrum is required for one species (H. lancifolium). In the present study twelve new species are proposed (H. bangueyense, H. caudifolium, H. collinum, H. ellipticifolium, H. glaberrimum, H. glabrum, H. lithophilum, H. palustre, H. rheophyticum, H. riparium, H. sampitense, and H. subulatum). In addition, one incompletely known species is mentioned.